Military badge collecting - Gaylor, John. (London : L. Cooper, 1996)
In this, the 6th edition of Military Badge Collecting, John Gaylor, who is the Honourary Secretary of the Military Historical Society, treats every aspect of this fascinating hobby.
Includes index.
Keywords: Great Britain. -- Army -- Insignia -- Collectors and collecting